Retrospective review of the periodic publication the «Humanization of training-educate process» (1996-2000 years) on the issues of labor and ecological education with schoolchildren (Pedagogy of Higher and Secondary Education, 2013)
Cherkashina L. A. Retrospective review of the periodic publication the «Humanization of training-educate process» (1996-2000 years) on the issues of labor and ecological education with schoolchildren.The article covers the issues of labour and ecological education of students of educational institutions on the pages of the collection of scientific works the «humanization of training-educate process» from 1996 to 2000. The author analyzed the works of teachers on the problems of the full and harmonious development of the personality, emphasizes the importance of environmental education, attention is focused on the labor education of students as a necessary factor of existence of the individual in society.
Keywords: collection of scientific periodicals; labour; environmental education, students of educational institutions; person